Alkaloids from Narcissus tazetta L. - SH Soleimani; F Bernard; M Amini; R Khavari- nezhad (Institue of Medicinal Plants, ACECR, 2007)
Background: Narcissus tazetta of the Amaryllidaceae is a monocotyledon, perennial and bulbous plant. This ornamental fragrant plant has various alkaloids that have shown anti tumor, anti virus and anticholinergic activities. Objective: In this study, we have investigated the alkaloids of the bulbs of Narcissus tazetta (post flowering) from Gilan province, north of Iran. Methods: Ethanolic extract of bulbs were prepared. Then the alkaloids were extracted with different solvents (Et2O, CHCl3, Na2CO3 solution) to yielding a brown gum. This extract was Done chromatography by TLC on silica gel. The separated alkaloids were identified by the study of their NMR, IR and MASS spectra. Results: The bulbs of Narcissus tazetta from Gilan province were found to contain homolycorine as the major alkaloid as well as tazettine and ismine. Conclusion: This is the first report of ismine identification in the N. tazetta whereas tazettine and demethylated derivative of homolycorine, that have medicinal properties, were found previously.